MODELING OF QUEUE LENGTH AT RAILWAY LEVEL CROSSING CLOSE TO A SIGNALIZED INTERSECTION (CASE STUDY: JAGIR WONOKROMO SURABAYA RAILWAY LEVEL CROSSING) - Nur Fajar Aprilia Sari; Hera Widyastuti (Journal of Civil Engineering, 2021)
In Indonesia, there are still many level crossings, namely between railways and highways. This will cause congestion, in the form of queue length of vehicles that stop due to the gate closing at the railway level crossing. In addition, level railway crossing located near a signalized intersection can also affect the performance of signalized intersections. This is due to the queue length of vehicle that can interfere with intersection. Based on the problem, it is necessary to build two models. The first model is between the gate closing time at level crossing with the length and speed of the train using multiple regression method. The second model is between the gate closing time at level crossing and the queue length of vehicles using a simple regression method. The result of first model shows that the gate closing time at level crossing has a positive relationship with the length of train and a negative relationship with the speed of train. The relationship among these three variabels is y = -2.083  + 0.637   + 249.930. Y is described as the gate closing time at level crossing, while x1 is the speed of train and x2 is the length of train. While the result of second model regarding the relationship between the gate closing time at level crossing with the queue length of vehicles has a positive effect in each direction. The relationship between two variabels is y = 1.2329x + 84.725 for East Jagir Wonokromo Street from east to west direction and y = 0.5176x + 24.44 for East Jagir Wonokromo Street from west to east direction. Y is described as the gate closing time at level crossing and xis described as the queue length of vehicles.